PENINGKATAN DAYA SAING INDUSTRI KREATIF UNGGULAN SULAWESI UTARA MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Ivonne Helena Putong (Universitas Lambung Mangkurat, 2021)
In 2015, Indonesia entered a new economic era in the Southeast Asian Region, namely the introduction to the Asean Economic Community (AEC). The role of the creative industry that is so large and significant must be maintained to be able to compete in the implementation of the AEC. This study aims to identify and recommend strategies for the creative and leading industries of North Sulawesi Province to improve competitiveness in the face of the AEC. To formulate alternative strategies to increase industrial competitiveness using SWOT analysis. Some creative industry players become informants through in-depth interviews. The list of questions consists of two parts. The first part deals with historical information on the establishment of a business. The second part is 26 question items that refer to the Diamond Model (DM). The results of the SWOT analysis, the pottery industry and the stage home industry are in quadrant I. It means that the company is implementing an SO strategy. The SO strategy is to utilize the company's internal strengths to attract external profits. In general, organizations will implement WO, ST or WT strategies to achieve situations where they can implement SO strategies. The existence of the ASEAN free market is a threat and also an opportunity that must be exploited. Human resources are a major factor in the creative industry. The results found a crisis of skilled and professional labor in the pottery industry and stilt houses. Most of the existing workforce is self-taught because it is a hereditary industry. Specifically for the stage home industry, attention needs to be paid to the continuity of wood raw materials and the licensing is simplified.